2015
DOI: 10.1002/adsc.201500310
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Coupling between Methylarenes and Ammonia: A Direct Approach to Aromatic Primary Amides

Abstract: Oxidative Coupling Between Methylarenes and Ammonia: A Direct Approach to Aromatic Primary Amides. -A FeCl 3-catalyzed direct oxidative amidation between methylarenes and aqueous NH 3 using a TBHP/TBAI oxidation system is presented. Both coupling partners are used in their native form avoiding prior functionalization.-(ZHAO, Z.; WANG*, T.; YUAN, L.; HU, X.; XIONG, F.; ZHAO, J.; Adv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…In 2007, the Li group reported the first example of an FeCl 2 -catalyzed CDC reaction between a benzylic C–H bond and an sp 3 C–H bond of 1,3-dicarbonyl compounds to form a C–C bond using di- tert -butyl peroxide (DTBP) as an oxidant . Subsequently, the Fu group described the first example of oxidative amidation of benzylic C–H bonds with carboxamides using FeCl 2 as a catalyst, whereas the Shi group showed that FeCl 2 was also capable of catalyzing the oxidative coupling of benzylic C–H bonds with arenes or vinyl acetates. , Recent advances in this field include the expanding work of other groups, for example, those of Chen, Bolm, Chen, and Zhao, using imidazoles, , sulfoximines, amines, or aqueous ammonia as coupling partners. The Chen group also developed the oxidative coupling of benzylic C–H bonds with indoles via iron catalysis .…”
mentioning
confidence: 99%
“…In 2007, the Li group reported the first example of an FeCl 2 -catalyzed CDC reaction between a benzylic C–H bond and an sp 3 C–H bond of 1,3-dicarbonyl compounds to form a C–C bond using di- tert -butyl peroxide (DTBP) as an oxidant . Subsequently, the Fu group described the first example of oxidative amidation of benzylic C–H bonds with carboxamides using FeCl 2 as a catalyst, whereas the Shi group showed that FeCl 2 was also capable of catalyzing the oxidative coupling of benzylic C–H bonds with arenes or vinyl acetates. , Recent advances in this field include the expanding work of other groups, for example, those of Chen, Bolm, Chen, and Zhao, using imidazoles, , sulfoximines, amines, or aqueous ammonia as coupling partners. The Chen group also developed the oxidative coupling of benzylic C–H bonds with indoles via iron catalysis .…”
mentioning
confidence: 99%
“…In the same year, Zhao and co‐workers extended their previous reaction conditions for the synthesis of primary aromatic amides from methylarenes and aqueous ammonia (Scheme ) . The authors found that the other ammonium salts such as NH 4 Cl, NH 4 HCO 3 , HCO 2 NH 4 , and (NH 4 ) 2 CO 3 were also worthwhile amine sources for this transformation.…”
Section: Synthesis Of Amides From Methylarenesmentioning
confidence: 98%
“…In path A, the aldehyde is converted to nitrile intermediate in the presence of oxidant and catalyst, subsequently nitrile intermediate undergoes hydration to afford the desired primary amide . In path B, the reaction of an aldehyde with an amine or its surrogate affords the hemiaminal intermediate, which undergoes subsequent oxidation to form the desired amide . Another attractive strategy is shown in Path C, which involves the cross‐coupling of acyl radical that generated from aldehyde and amino radical that generated from an amine or amine surrogate to provide the desired amide product …”
Section: Synthesis Of Amides From Methylarenesmentioning
confidence: 99%
“…To address these issues, more practical and efficient methods have been developed. For example, the employment of activators for the conversion of carboxylic acids into amides, metal-catalyzed hydration of nitriles, the rearrangement of aldoximes, Pd-catalyzed aminocarbonylation of aryl halides, C–C bond cleavage of ethylarenes, decarboxylative ammoxidation of phenylacetic acid, oxidation of primary benzyl amines, and oxidative amidation of aldehydes, benzyl alcohols, methyl ketone, or methylarenes . However, there are no reports that secondary or tertiary amides have been employed as a starting material toward the synthesis of primary amides with the exception of those using a deprotection process.…”
mentioning
confidence: 99%